2019
DOI: 10.3390/ijerph16030424
|View full text |Cite
|
Sign up to set email alerts
|

Active and Passive Use of Green Space, Health, and Well-Being amongst University Students

Abstract: Frequent exposure to green space has been linked to positive health and well-being in varying populations. Yet, there is still limited research exploring the restorative benefits associated with differing types of green space use among students living in the university setting. To address this gap, we explored green space use amongst a population of undergraduate students (n = 207) attending a university with abundant opportunities to access the restorative properties of nature. The purpose of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
93
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(129 citation statements)
references
References 51 publications
4
93
1
1
Order By: Relevance
“…We cannot assume similar effects would be seen in older populations, non-healthy (i.e., clinical) populations, or individuals without ready access to outdoor nature, including people with physical limitations. Because most experimental research involving responses to natural environments (Holt et al, 2019;Mygind et al, 2019) and VR (Oh et al, 2016) use college student populations, our findings still build on the existing body of literature on the therapeutic potential of 360-degree nature videos in VR.…”
Section: Strengths and Limitationsmentioning
confidence: 85%
“…We cannot assume similar effects would be seen in older populations, non-healthy (i.e., clinical) populations, or individuals without ready access to outdoor nature, including people with physical limitations. Because most experimental research involving responses to natural environments (Holt et al, 2019;Mygind et al, 2019) and VR (Oh et al, 2016) use college student populations, our findings still build on the existing body of literature on the therapeutic potential of 360-degree nature videos in VR.…”
Section: Strengths and Limitationsmentioning
confidence: 85%
“…We found that user groups (i.e., Hgroup and Mgroup) were more motivated by "to exercise and hike" than the LNgroup. Considering that health has been recognized as one of the most important life domains [115,116] and that the study area is a densely urbanized environment with a lack of space for exercising, the higher SWB of user groups than the LNgroup can be explained by the satisfaction of the health motivation of visitors to UGS. Compared to user groups, respondents in the LNgroup reported higher motivations "to rest," "to be away from home," and "to spend time with family members."…”
Section: Motivation and Constraintmentioning
confidence: 99%
“…However, it is noteworthy that some studies have reported that the amount of time spent is as important for SWB as frequency of visit (e.g., [115,[138][139][140][141]). For example, university students who reported longer amounts of time spent in green spaces showed high levels of life satisfaction and low levels of stress (e.g., [115,139]).…”
Section: Effects Of Frequency Of Visits and Time Spent In Ugs On Swbmentioning
confidence: 99%
See 2 more Smart Citations